A Novel Captopril-hydrochlorothiazide Solid Dispersion - Priya, S. Padma; Rajendran, N. N. (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
The earlier studies reveal that only physiologically inert carriers have been used to effect solid dispersion with improved dissolution of poorly soluble drugs. In the present study, a novel drug – drug solid dispersion approach was applied to prepare solid dispersions in proportions similar to commercial preparations of hydrochlorothiazide and captopril (HCT-CAP) combination. The poorly soluble hydrochlorothiazide was solid dispersed in soluble captopril by kneading method. The solid dispersion was characterised for TLC, spectrophotometric assay, infra-red spectra, DSC and X-ray diffractometry. The influence of captopril on solubility of hydrochlorothiazide was assessed by solubility studies. The solid dispersions were evaluated for in vitro dissolution characteristics and the results were compared with that of physical mixtures of HCT-CAP and pure hydrochlorothiazide. The dissolution rate of hydrochlorothiazide from solid dispersions was found to be faster than that of physical mixtures and pure drug. Particle size reduction, micro-environmental solubilisation, change in the crystalline nature of hydrochlorothiazide and formation of solid solution are the probable mechanisms for enhanced dissolution of hydrochlorothiazide.